Achieving teamwork in naturalistic sport settings: An exploratory qualitative study of informational resources supporting football players' activity when coordinating with others. (September 2018) - Feigean, Mathieu; R'Kiouak, Mehdi; Seiler, Roland; Bourbousson, Jérôme
Abstract: This study aimed to provide a deeper understanding of the nature of informational resources that support team members' activities when contributing to spatiotemporal collective behaviour in real time. To this end, we conducted an exploratory qualitative study of a naturalistic football setting in which an enactivist approach to teamwork is employed. Ten professional football players participated in this study. Based on a continuous video recording of the participants' activities during an entire game and using phenomenological interview techniques, we performed a thematic analysis of the players' activities as experienced by them. Many situational resources have been highlighted based on the themes captured in the analysis; these have been categorised from local to global information and include the simultaneous use of these resources by the players. Only one theme reflecting knowledge-based resources did not cover situational resources. The results are discussed in terms of focalised versus broad awareness, nearby space-based versus relocated informational resources and local versus global informational resources. Highlights: Players' activities are supported by many different informational resources. Informational resources are categorised by themes from local to global. Players' awareness of resources represent different degrees of focalisation.